The Role of Postoperative Radiotherapy and Prognostic Model in Primary Squamous Cell Carcinoma of Parotid Gland - Qiu, Wenlong; Yang, Yong; Sun, Shiran; Zhou, Fengge; Xu, Yi; Luo, Xi; Wang, Zekun; He, Meilin; Liu, Yang; Yi, Junlin (Frontiers in Oncology, 2021)
Background: Primary squamous cell carcinoma of parotid gland (parotid SCC) is a high malignant histologic subtype of parotid cancers with aggressive clinical presentation. However, the clinical features and survival benefit of postoperative radiotherapy (PORT) for primary parotid SCC are not well known. Methods: A retrospective population-based study was performed to identify the role of PORT in parotid SCC patients diagnosed between 1975 and 2016 from SEER database. A prognostic risk model was established based on patient clinical features, including age, tumor stage and node involvement status. Patients were stratified into high-, intermediate- and low risk according to this model. The survival benefit of radiotherapy was compared in the whole cohort and different risk groups. Results: 931 parotid SCC patients were extracted from SEER database, 634 (68.1%) in the RT group and 286 (30.7%) in the non-RT group. Overall, 503 (54.0%) deaths occurred, with a median follow-up of 84 months, the 5-year OS was 43.6% in the whole cohort, 47.7% vs 35.9% in patients with/without PORT (P=0.005), and 58.9% vs. 38.8% vs. 27.1% in low-, intermediate- and high-risk group (P<0.001). Compared with surgery alone, PORT significantly improved the OS of patients with medium risk (47.5 vs. 20.6, P<0.001), whereas not in the low risk (61% vs. 54%, P=0.710) and high (25.6% vs. 28.7%, P=0.524). Conclusion: This prognostic model can separate the patients with parotid squamous cell carcinoma into different risk. PORT significantly improved the OS of patients with intermediate risk, whereas high risk group may need more intensive treatment strategies.